Condition of Specific Immunity to Pertussis in Different Age Groups of Children - A. A. Basov; O. V. Tsvirkun; A. G. Gerasimova; N. V. Rossoshanskaya; V. N. Babenko (Эпидемиология и вакцинопрофилактика)
The present study of antipertussis immunity stress and level in young and school children who was vaccinated ADTP vaccine showed that on the average 28.3% of them were seronegative. The lowest parts of seronegative children were detected in the age group of infants under 12 months of age (12.3%) and in that of 15 - 17 years old teenagers (12.1%). The maximum percent of seronegative children were detected in the age group of 6 - 8 years - 38.8%. Despite the nonsignificant increase of this indicator, compared to the previous age group, it is advisable to supplement serological monitoring of indicator group 6- 7 years. The researchers did not discover the reliable correlation between the pertussis incidence in different age groups and proportion of seronegative children in those groups. The obtained results suggest that there is an occult circulation of pertussis causing agent. They also showed that it is necessary to revise the indicator age groups for serologic monitoring of antipertussis immunity.